SARS-CoV-2-specific humoral and cell-mediated immune responses after immunization with inactivated COVID-19 vaccine in kidney transplant recipients (CVIM 1 study) - Bruminhent J. (2023)
Immunogenicity following inactivated SARS-CoV-2 vaccination among solid organ transplant recipients has not been assessed. Seventy-five patients (37 kidney transplant [KT] recipients and 38 healthy controls) received two doses, at 4-week intervals, of an inactivated whole-virus SARS-CoV-2 vaccine. SARS-CoV-2-specific humoral (HMI) and cell-mediated immunity (CMI) were measured before, 4 weeks post-first dose, and 2 weeks post-second dose. The median (IQR) age of KT recipients was 50 (42–54) years and 89% were receiving calcineurin inhibitors/mycophenolate/corticosteroid regimens. The median (IQR) time since transplant was 4.5 (2–9.5) years. Among 35 KT patients, the median (IQR) of anti-RBD IgG level measured by CLIA after vaccination was not different from baseline, but was significantly lower than in controls (2.4 [1.1–3.7] vs. 1742.0 [747.7–3783.0] AU/ml, p <.01) as well as percentages of neutralizing antibody inhibition measured by surrogate viral neutralization test (0 [0–0] vs. 71.2 [56.8–92.2]%, p <.01). However, the median (IQR) of SARS-CoV-2 mixed peptides-specific T cell responses measured by ELISpot was significantly increased compared with baseline (30 [4–120] vs. 12 [0–56] T cells/106 PBMCs, p =.02) and not different from the controls. Our findings revealed weak HMI but comparable CMI responses in fully vaccinated KT recipients receiving inactivated SARS-CoV-2 vaccination compared to immunocompetent individuals (Thai Clinical Trials Registry, TCTR20210226002).